Pola Asuh Orang Tua terhadap Kemampuan Bina Diri Anak Disabilitas Intelektual - Sari, Silvia Yustika; Sukmawati, Bhennita; Nurhadiyati, Arifah (JOEAI (Journal of Education and Instruction), 2025)
This research aims to identify the type of parenting style applied and analyze the impact of parenting styles on children's self-development abilities. The method used is a descriptive qualitative method, where data is collected through interviews, observations, and documentation on parents of students at the Jember State Special School, using a purposive sampling technique. The results of the research show that the parenting style provided by two parents on the self-development abilities of children with intellectual disabilities at the Jember State Special School, namely that parent R applies a combination of authoritarian parenting and democratic parenting. This parenting style can help develop children's self-development abilities well. Meanwhile, M's parents use a permissive parenting style, which can hinder the child's self-development skills. The conclusion of this research shows that parenting styles have an essential role in the self-development abilities of children with intellectual disabilities at the Jember State Special School.   Keywords: Parenting Patterns, Self-Development, Intellectual Disabilities